Pengaruh Harga, Fasilitas, Pengeluaran Konsumen, Dan Anggota Jumlah Keluarga Terhadap Permintaan Rumah KPR Bersubsidi Kecamatan Alalak Kabupaten Batola - Jumriyanor; Rusdiansyah (PPJP ULM, 2020)
The research was conducted to find out: 1. How the price, facilities, consumer spending,and the household number had on subsidized home demand. 2. Which factor is mostdominant affecting the market of subsidized home MORTGAGES.This method of research uses quantitative and qualitative approaches. Variables or factorsaffecting the demand for a home translated in numbers will be analyzed with a quantitativeapproach. Still, information from consumers that cannot be solved in numbers will bedepicted in a qualitative narrative.The results showed that the facility factor, consumer spending was influential on demandfor subsidized homes in the district Alalak Barito Kuala District, stated that the mostsignificant factor is the consumer spending factor With a result of the calculated T 2,453and the second is the facility factor with a result of the count of 2,082. Simultaneously thewhole of variables X1, X2, X3, X4. Effect on the Y of the test results F, F count of 4,302.Means the price, facilities, consumer spending, and the number of simultaneous familiespositively affect the demand for subsidized homes in the sub-district of Batola district.